Measurement of inductance in switch reluctance (SR) motor: article / Nurita Ismail - Ismail, Nurita (2011)
This thesis presents the measurement of inductances for two phases 4/6 pole switched reluctance (SR) motor. This project is mainly focused in laboratory measurement and data analysis to measure the inductance of SR motor. The current and voltage waveform need to be measured in lab in order to do the integration of flux by using MATLAB software. Then the unsaturated inductance for rotor position can be obtained by the slope of linear part of the flux linkage versus current curve. Finally, the laboratory experiment results will be compared with finite element analysis that can be obtained by using the 2D Finite Element Method Magnetic (FEMM) program.